The brink - Cooper, Benjamin; Thunderhead Entertainment (California : Thunderhead Entertainment, 2005)
Thomas Alva Edison died on October 1931, but not before completing his greatest invention, a device for talking to the dead. Though to be lost forever, tracks down the legendary blueprints. She rallies a group of friends to built it in a dilapidated house
Title from title screen
Executive producer, Robyn Cooper
Cast: Rachel Balzer, Jeff Ryan, Jason Flowers, Heather Chase
DVD format
With optional Malay or Chinese subtitles
Keywords: Ghosts in motion pictures; Suspense in motion pictures